Progress on role of ion channels of cardiac fibroblasts in fibrosis - Xing, Chenxv; Bao, Limeng; Li, Weidong; Fan, Hongkun (Frontiers in Physiology, 2023)
Cardiac fibrosis is defined as excessive deposition of extracellular matrix (ECM) in pathological conditions. Cardiac fibroblasts (CFs) activated by injury or inflammation differentiate into myofibroblasts (MFs) with secretory and contractile functions. In the fibrotic heart, MFs produce ECM which is composed mainly of collagen and is initially involved in maintaining tissue integrity. However, persistent fibrosis disrupts the coordination of excitatory contractile coupling, leading to systolic and diastolic dysfunction, and ultimately heart failure. Numerous studies have demonstrated that both voltage- and non-voltage-gated ion channels alter intracellular ion levels and cellular activity, contributing to myofibroblast proliferation, contraction, and secretory function. However, an effective treatment strategy for myocardial fibrosis has not been established. Therefore, this review describes the progress made in research related to transient receptor potential (TRP) channels, Piezo1, Ca2+ release-activated Ca2+ (CRAC) channels, voltage-gated Ca2+ channels (VGCCs), sodium channels, and potassium channels in myocardial fibroblasts with the aim of providing new ideas for treating myocardial fibrosis.